Petaloid technique and prognostic significance of macular hole shapes by optical coherence tomography for full thickness macular hole - Keyal, Khusbu; Li, Bing; Liu, Chunyu; Tian, Zhongping; Li, Houshuo; Bi, Yanlong (Frontiers in Medicine, 2024)
Surgical advancements for full-thickness macular hole (FTMH) treatment include vitrectomy, membrane peeling, and the inverted flap technique (IFT). IFT, which involves inverting the internal limiting membrane (ILM) flap over the macular hole (MH) or into the MH, improves success rates and visual recovery. However, issues like mis-aspiration during flap handling have been problematic. We introduce the petaloid technique, to position the ILM flap under air during FTMH surgery to evaluate its outcomes. This retrospective study included 28 eyes, with a mean minimum linear diameter (MLD) 472.04 ± 199.7 μm and basal diameter (BD) of 834.95 ± 593.54 μm. Primary closure of MH was achieved in 96.42% of patients, with 3.57% showing persistent MH during the 6-month follow-up. The VA improved significantly from preoperative levels at each postoperative stage, with notable increases at 3 months (0.86 ± 0.49 logMAR; p = 0.0132) and 6 months (0.77 ± 0.41 logMAR; p = 0.000081). The new closure patterns showed Type A in 28.6%, B in 14.3%, C in 28.6%, and D in 25%. Among different types of closure patterns, although VA improved in all types, significant improvement in VA was noted for type A and type C, with notable improvements at the 6-month follow-up for Type A (0.60 ± 0.23 logMAR; p = 0.02) and at the 1-month follow-up for Type C (0.62 ± 0.28 logMAR; p = 0.02). For macular hole retinal detachment in 5 eyes, the average preoperative VA was 1.86 ± 0.19 logMAR, while the final mean postoperative VA showed a significant improvement to 1.1 ± 0.40 logMAR (p = 0.021, paired t-tests). Retinal reattachment was achieved in all cases (5/5) without recurrent detachment post-silicone oil removal. For the prognostic significance of MH shapes identified by OCT, it can be concluded that the shape of macular holes significantly influences visual acuity outcomes at 6 months post-surgery (p = 0.037). The shape of macular holes, particularly Flask-shaped, significantly impacts visual acuity compared to other shape. The modified petaloid technique for treating FTMH proved safe and effective, with no significant complications noted.